Prognostic impact of examined lymph node count in pT1N0M0 esophageal cancer: A population‐based study. Issue 7 (24th June 2019) - Liu, Ying; Yang, Heli; Fu, Hao; Li, Meng; Feng, Zhen; Peng, Zhongmin; Liang, Zhen; Wang, Hui
Abstract : Background: Research on the impact of examined lymph node (ELN) count on node‐negative esophageal cancer (EC) especially pT1N0M0 EC is inadequate. This study was designed to analyze the prognostic impact of ELN count on pT1N0M0 EC. Methods: Data of resected pT1N0M0 EC patients between 1988 and 2015 were extracted from the United States Surveillance, Epidemiology, and End Results (SEER) database. The association between ELN count and overall survival (OS) or esophageal cancer‐specific survival (ECSS) were investigated. Factors that may predict the outcome were identified using the Kaplan‐Meier method and the Cox proportional‐hazards model. Results: A total of 906 patients who underwent resection with at least one lymph node (LN) retrieved met our criteria. The cumulative 5‐year OS was 67.6%, while the cumulative 5‐year ECSS was 75.4%. X‐Tile analysis showed that 12 was the optimal cutoff value for ELN count in terms of both OS (χ2 = 28.764, P < 0.0001) and ECSS (χ2 = 15.668, P = 0.0026). A Kaplan‐Meier survival analysis and log‐rank comparison revealed that ELN > 12 was significantly associated with better OS (HR, 0.532; 95% CI, 0.421–0.672; P < 0.001) and ECSS (HR, 0.561; 95% CI, 0.420–0.749; P < 0.001) rates than ELN ≤12. The OS and ECSS benefit of increasing ELN count were also reflected in the multivariate analysis after adjustment for age, sex, race, marital status, location, T stage, tumor size, pathology, and differentiation. Conclusions: These findings indicated that greater number of ELN count exhibits prognostic significance in pT1N0M0 EC. We recommend more than 12 LNs should be examined in pT1N0M0 EC.